A comparison of craniofacial Class I and Class II growth patterns. - Riesmeijer, Arnold M; Prahl-Andersen, Birte; Mascarenhas, Anna K; Joo, Bert H; Vig, Katherine W L (American Journal of Orthodontics & Dentofacial Orthopedics, 2004)
Longitudinal craniofacial databases, including the Fels Longitudinal Study, the Michigan Growth Study, and the Nijmegen (The Netherlands) Growth Study, were compared for a set of 12 craniofacial measurements on lateral skull cephalograms. The age ranges of the subjects were 7-14 years for females and 9-14 years for males. When we compared the normally distributed databases using multiple comparisons, a small sample test statistic t for differences between means of the databases showed few statistical differences. The databases were therefore pooled, and sex-specific Class I (ANB < 4 degrees), and Class II (ANB > or = 4 degrees) subsamples were analyzed with the same t test. The sizes of these subsamples ranged from 39 to 122 at the different ages. The findings showed that the Class II samples had greater SNA and SN-GoMe angles. Compared with the Class I group, shorter mandibles were found in the younger age groups of the Class II samples. No differences were found in mandibular length (Ar-Gn) and mandibular body length (Go-Gn) in the older Class II groups compared with the Class I groups. These findings indicate that the greater mandibular lengthening in the Class II groups might have contributed to successful Class II treatment in studies in which a Class I group was the control. Because of individual biological variability, the average Class I or Class II growth pattern might not be a realistic assumption or have clinical relevance for individual patients.